QUALITY MANAGEMENT IN HIGHER EDUCATION: SYSTEMATIC LITERATURE REVIEW AND META ANALYSIS - Anas Nasrudin; Naf'an Tarihoran; Enung Nugraha (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Higher education currently faces complex challenges in efforts to improve the quality of educational services amidst increasingly fierce global competition. This research aims to conduct a systematic literature review and meta-analysis of various current research on higher education quality management to produce a comprehensive model that integrates various approaches and considers local context and religious values. The research method uses a qualitative approach with Systematic Literature Review (SLR) and Meta-Analysis, implementing the PRISMA protocol as a methodological framework in literature selection. Of the initial 59,422 articles searched, 7 high-quality articles were selected for comprehensive review. The meta-analysis results show a significant positive correlation between quality management factors and the quality of higher education with an overall effect size of r = 0.60 (95% CI [0.52, 0.68]). Transformative leadership emerged as the most influential factor (r = 0.68), followed by quality culture (r = 0.63) and TQM implementation (r = 0.62). Moderate to high heterogeneity (I² = 67.3%) indicates the need for a contextual rather than standard quality management approach. These findings suggest a holistic quality management model that integrates TQM principles, CIPP evaluation model, transformative leadership, outcome-based curriculum development, stakeholder involvement, and integration of religious values ​​according to institutional characteristics.